Description of a new species of the genus Bagauda (Heteroptera: Reduviidae: Emesinae) from Maharashtra State, India - Ghate, Hemant V.; Boyane, Swapnil S.; Joshi, Nikhil U. (Zootaxa, 2019)
A new Emesinae species, Bagauda atypicus sp. nov., is described from Maharashtra, India. It is an atypical member of the genus Bagauda and the tribe Leistarchini because both male and female are micropterous and display a character not found in any Leistarchini described so far, namely presence of prominent, erect and blunt, humeral tubercles. The species is cavernicolous because the specimens were collected in old caves. Association with spider webs was observed.